Cuff Anastomosis of Both Renal Artery and Vein to Minimize Thrombosis: A Novel Method of Kidney Transplantation in Mice. Issue 1 (2nd January 2022) - Yu, Yi; Li, Jun; Bi, Zirong; Wu, Chenglin; Yang, Shicong; Jiang, Qifeng; Deng, Ronghai; Fu, Qian; Liu, Longshan; Wang, Changxi
Abstract: Objectives: Anastomosis of renal artery and renal vein in mouse models of kidney transplantation is technically challenging. Conventional technique using suture may result in vascular thrombosis. We developed a simple cuff method to anastomose both renal artery and vein. Materials and Methods: Briefly, the left renal artery was occluded at the junction with abdominal aorta using a small vessel clip, transected at the renal hilum, irrigated with heparinized saline, and passed through the lumen of a seamless tubing made of polyimide. The loose end of the artery was everted over the cuff and secured using an 8-0 silk suture. The cuffed artery was inserted into the donor renal artery and secured with an 8-0 suture. Anastomosis of the renal vein was performed similarly. Isograft transplantation was conducted using BALB/c mice as donor and recipient mice (n = 20). The total operative time was 77 ± 3 min, and the cold ischemic time of the graft kidney was minimized to 20 min. One animal was excluded due to anatomic variant vessels and another one died at three day after surgery without thrombosis. Results: Serum creatinine increased insignificantly after transplantation and remained stable over 12 weeks posttransplant. Five recipient mice were sacrificed for histologic examination at 12 weeks after transplantation. No vascular thrombosis was observed at the site of anastomosis. The isografts showed no evidence of acute and chronic lesions such as extinctive ischemic sclerosis and interstitial fibrosis. Conclusion: In summary, cuff anastomosis can be used to eliminate thrombosis formation in the mouse model of kidney transplantation.